Uji Homogenitas dengan Sebaran Khi-Kuadrat dalam Evaluasi Suatu Sistem - Iwa Sungkawa (ComTech: Computer, Mathematics and Engineering Applications, 2011)
This paper discusses the application of khi-square distribution in homogeneity of variance test on the control of a system used in a process considered normally spread with a mean of and a variance (degree of homogeneity) of . It is necessary to test the hypothesis statistically Ho: with the average μo value is unknown, and the statistic used is Khi-square distribution. On this occasion, an evaluation is executed upon a "Matsuyama" stabilizer (standard volt single phase (L)) to be used in Srengseng, Lenteng Agung, South Jakarta. Based on the test results of upon the variance with average standard voltage 220 volt, the electricity consumers in Srengseng are encouraged to use the stabilizer for household appliances that require voltage stability. By examining the voltage fluctuations at the location and stabilizer conditions (input range), the test result carried out through variance similarity test states that “Matsuyama” stabilizer is eligible and applicable in the area.